Strategi Komunikasi Pemasaran Produk Desain Rumah Untuk Meningkatkan Produktivitas Penjualan Di CV Visual Karya Utama - Arif Bachtiar; Briel Ksatria Pradana; Margaretha Evi Yuliana (Journal Of Informatics And Busisnes, 2023)
Home Product Design to Increase Sales Productivity on CV Visual Karya Utama. The purpose of this study is to find out how the marketing communication strategy is applied to increase sales of CV Visual Karya Utama's sales products and what are the influencing factors of the marketing communication strategy. This research uses a descriptive method. Data obtained from information through interviews with CV Visual Karya Utama employees. The research results obtained are that CV Visual Karya Utama implements a strategy to increase sales by becoming a design site that is known to many people. CV Vida Karya Utama has many advantages to attract many consumers. Improve sales promotion methods so that many customers order the CV Visual Karya Utama model. Supporting factors in product marketing are domestic designs, where product prices are more affordable and comprehensive, and the capital spent is relatively small. Factors that hinder CV Visual Karya Utama are the availability of models which sometimes sell out, lack of staff, ineffective managers, lack of advertisements uploaded to social media. Based on the results above, it is expected that CV Visual Karya Utama will continue to improve its marketing communication strategy so that revenue will increase.